Optimal loading during two different leg-press movements in female rowers - Lund, R. J.; Dolny, D. G.; Browder, K. D. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The purpose of this study was to determine the optimal load for power during concentric only (CO) and stretch-shortening cycle (SSC) leg-press movements during the initial portion of the concentric phase as well as throughout the entire concentric phase in trained female rowers. METHODS: Thirty female rowers (age = 19.6 +/- 1.2 yr) were tested for strength (1RM), mean power (MP), peak power (PP), as well as power output at 50, 100, 150, and 200 ms (P50-P200) during both CO and SSC leg-press movements and across six different loads (30-80% 1RM) on the Omnikinetic dynamometer. RESULTS: Split-split plot analysis indicated that MP and PP were maximized at approximately 60% 1RM in both CO and SSC movements. There were no significant differences in P50 and P100 across all loads for both CO and SSC. P150 was greatest at 30, 40, 50, and 60% 1RM for CO and SSC movements. P200 was maximized at 30, 40, and 50% 1RM during CO. P200 was maximized at 50, 60, and 70% 1RM during SSC. CONCLUSIONS: There was no difference in the optimal loads for MP (40, 50, and 60% 1RM) and PP (50, 60, and 70% 1RM) between CO and SSC movements. An enhancement of power during the initial 200 ms of the concentric phase of SSC movements was observed. Greater time to reach PP was the reason for the enhancement in PP output observed in CO movements. The CO training regimen associated with the sport of rowing also may have lessened the effect of the SSC.